2018
DOI: 10.1080/10253866.2018.1512245
|View full text |Cite|
|
Sign up to set email alerts
|

Motherhood in migration: schools as acculturation agents

Abstract: Motherhood roles lie at the intersection of gender, professional, family, and social identities and are highly contextualized in culture, making them particularly relevant for acculturation success. We provide an empirical example of how schools act as acculturation agents, using the experiences of career-oriented migrant mothers whose children attend elite private schools in Santiago, Chile. This study contributes to consumer acculturation research and to research on matricentric feminism, which positions mot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 50 publications
0
15
0
1
Order By: Relevance
“…In Table 4, we present the research strategies of the studies that make up our corpus. Ethnographic studies are the most incisive in our corpus: when online interviews appear in works from the three levels of our category: those that use DTIC to collect research data (Alhashem et al, 2021;Campbell et al, 2019;Corciolani, 2014;Gordon-Wilson, 2021;Kozinets et al, 2016;Le-Phuong Nguyen et al, 2017;Obiegbu et al 2019;O'Leary & Murphy, 2019;Podoshen et al, 2014 ;Reid & Duffy, 2018;Yalkin & Veer, 2018); use virtual dialogues as a complement to in-person interviews (Athwal & Harris, 2018;Chimenti, 2020;Darmody et al, 2017;Dean, 2019;Dolbec & Fischer, 2015;Figueiredo & Scaraboto, 2016;Harwood & Garry, 2010;;Husemann & Eckhardt, 2019;Nilsson, 2020;Pulh et al, 2018;Rojas Gaviria et al, 2019;Sandes et al, 2019;Scaraboto, 2015;Scarborough & McCoy, 2016;Veer & Golf-Papez, 2018;Veresiu & Giesler, 2018;Zanette & Brito, 2019); and those who resorted to the technique as an option not initially planned for the scope of the research (Beverland et al, 2020;Feiereisen et al, 2020;Giesler & Veresiu, 2014;McAlexander et al, 2014). Specifically, we identified that online interviews are often associated with a stage or complement of netnography -the adaptation of the ethnography developed by Kozinets (2020) consumption practices in the virtual context.…”
Section: Research Strategymentioning
confidence: 99%
See 1 more Smart Citation
“…In Table 4, we present the research strategies of the studies that make up our corpus. Ethnographic studies are the most incisive in our corpus: when online interviews appear in works from the three levels of our category: those that use DTIC to collect research data (Alhashem et al, 2021;Campbell et al, 2019;Corciolani, 2014;Gordon-Wilson, 2021;Kozinets et al, 2016;Le-Phuong Nguyen et al, 2017;Obiegbu et al 2019;O'Leary & Murphy, 2019;Podoshen et al, 2014 ;Reid & Duffy, 2018;Yalkin & Veer, 2018); use virtual dialogues as a complement to in-person interviews (Athwal & Harris, 2018;Chimenti, 2020;Darmody et al, 2017;Dean, 2019;Dolbec & Fischer, 2015;Figueiredo & Scaraboto, 2016;Harwood & Garry, 2010;;Husemann & Eckhardt, 2019;Nilsson, 2020;Pulh et al, 2018;Rojas Gaviria et al, 2019;Sandes et al, 2019;Scaraboto, 2015;Scarborough & McCoy, 2016;Veer & Golf-Papez, 2018;Veresiu & Giesler, 2018;Zanette & Brito, 2019); and those who resorted to the technique as an option not initially planned for the scope of the research (Beverland et al, 2020;Feiereisen et al, 2020;Giesler & Veresiu, 2014;McAlexander et al, 2014). Specifically, we identified that online interviews are often associated with a stage or complement of netnography -the adaptation of the ethnography developed by Kozinets (2020) consumption practices in the virtual context.…”
Section: Research Strategymentioning
confidence: 99%
“…Specifically, we identified that online interviews are often associated with a stage or complement of netnography -the adaptation of the ethnography developed by Kozinets (2020) consumption practices in the virtual context. Furthermore, we observed two studies that use another naturalistic method, autoethnography (Dean, 2019;Rojas Gaviria et al, 2019), complemented by interviews via DTIC.…”
Section: Research Strategymentioning
confidence: 99%
“…This idea of identity construction also forms the basis of more critical studies that reflect on the constraints consumers face when performing an identity project. These studies show how, occasionally, consumers' strategizing and improvising prove to be ineffective (Rojas-Gaviria et al, 2019;Shankar et al, 2009). Hence, although consumption routines are seen as empowering resources (Schau et al, 2009) in consumers' quest for identity-making, they are also seen as hindering obstacles for the same (The Voice Group, 2010).…”
Section: Poetizing and Consumer Representation The Need For Poetizing Within Identity Projectsmentioning
confidence: 99%
“…Scholars have argued that a school was an institution where children and youths learn from one another to the extent to which the acculturation types of entire families changed (Gaviria et al, 2018). As Berry et al (2002) investigated, in the process of acculturation, there are changes in behaviour, cognitive and emotion.…”
Section: Introduction and Background Of The Studymentioning
confidence: 99%